Correction: The sarcoma ring trial: a case-based analysis of inter-center agreement across 21 German-speaking sarcoma centers (Journal of Cancer Research and Clinical Oncology, (2025), 151, 1, (30), 10.1007/s00432-024-06063-z) - Roohani, Siyer; Handtke, Jolina; Hummedah, Kamal; Albertsmeier, Markus; Andreou, Dimosthenis; Apostolidis, Leonidas; Augustin, Marinela; Bauer, Sebastian; Billner, Moritz; Bösch, Florian; Deinzer, Christoph K.W.; Deventer, Niklas; et al. (Journal of Cancer Research and Clinical Oncology, 2025)
In this article, the author’s name Armin Tuchscherer was incorrectly written as Armin Tuscherer. The original article has been corrected.
CRIS-Team Scopus Importer:2025-05-02